Formati in potenciali lokalne "male skupnosti" - Dobovšek, Zala (Amfiteater (Ljubljana), 2022)
The article focuses on the phenomena, developments and potentials of small arts (Kleinkunst) in the Slovenian space. Small arts are a form of artistic response that, through diverse performance genres – such as cabaret, new burlesque, improvisational theatre, stand-up, interventions in public space, contemporary circus, drag, queer and LGBTQI+ stage events – provides a social commentary on the existing traditionalist, heteronormative, patriarchal and capitalist society. The article elaborates the term small arts and its artistic and social elements and tries to identify it concretely in the local space. This broad umbrella term is characterised by the heterogeneity of its themes and aesthetics. In Slovenia, it has an even more specific undertone and position, as its development and influence are hampered by a small population. When selecting the creators of small arts, the author focused mainly on those working in the sphere of the non-governmental sector, who create continuously, have artistic credibility and are not market-oriented.
Keywords: alternative theatre; alternativno gledališče; kleinkunst; kvir; LGBTQI+; male umetnosti; queer; redramatizacijaLGBTQI+; small arts